The magnitude of correlation between deadlift 1RM and jumping performance is sports dependent - Schiemann, Stephan; Keiner, Michael; Wirth, Klaus; Lohmann, Lars H.; Wagner, Carl-Maximilian; Behm, David G.; Warneke, Konstantin (Frontiers in Sports and Active Living, 2024)
Based on the assumption of maximal strength as a basic ability, several studies show a high influence of maximum strength on jumping performance in several sport athletes. However, there is a wide range of correlations from r = 0.17 -0.9 between squat 1RM and jumping performance in different sports. Additionally, there are only a few studies investigating the influence of deadlift one repetition maximum (1RM) on jumping performance. Thus, this study aimed to investigate the correlations between 1RM in the deadlift on jumping performance using the countermovement jump height (CMJ) and squat jump height (SJ) considering different sports. Therefore, 103 athletes with experience in the deadlift from soccer, basketball, American football, powerlifting as well as participants from different sports without any deadlift experience (control group) were included to this study. Overall statistics showed a significant moderate influence of deadlift 1RM (r = 0.301 -0.472) on jumping performance. However, subgroup analysis showed no significant correlation between deadlift 1RM and jumping performance in control participants, while moderate correlations could be detected in powerlifters (r = 0.34 -0.39), soccer players (0.437 -0.46), American football players (0.584 -0.62) and high correlations in basketball players (r = 0.809 -0.848) showing significant influence of type of sport on correlations between deadlift maximum strength and jumping performance. Therefore, results underline movement velocity-and task specificity of strength training routines.